IMPLEMENTATION OF CUSTOMER SERVICE STANDARDS AT PT. BPRS BANDAR LAMPUNG AND PT. SRB METRO MADANI - Patimah, Siti (Perpustakaan dan Penerbitan Unismuh Makassar, 2019)
Customer service standards at conventional banks are not always maximally applied. This makes customers from the middle to lower economic level less satisfied, even the majority of objections with some of the bank's regulations. This could be the reason for the lower economic level people are reluctant to open savings in conventional banks. As for the middle economic level people open savings in conventional banks, do not fully entrust their financial management to the bank. One of the requirements to become an employee of a private company is relatively often used as a reason for the community to open savings in conventional banks. Relative people choose Islamic banks as a solution for their financial management. Appointed by PT. BPRS Bandar Lampung and PT. BPRS Metro Madani as a sample, in order to know the implementation of customer service standards, so that relatively many people open savings at the two banks. Qualitative methods are utilized in research. Observations, interviews, and documentation are used as data collection techniques, then the data are analyzed descriptively qualitatively. The results showed that the employees of PT. BPRS Bandar Lampung and PT. BPRS Metro Madani has and applies customer service standards based on sharia regulations. The research can be continued in a deeper discussion, namely about the implementation of the real application of Islamic business ethics in sharia-based institutions in improving the performance of the bank PT. BPRS Bandar Lampung and PT. BPRS Metro Madani'.